AIAA Atmospheric Flight Mechanics Conference and Exhibit 2002
DOI: 10.2514/6.2002-4511
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Nonlinear Aerodynamic Characteristics of Tandem-Control and Rolling-Tail Missiles

Abstract: fin deflection angle, deg Predicted nonlinear aerodynamic characteristics of roll angle, deg several canard-body-tail missile models are presented fin set roll angle with respect to body-fixed and compared to wind tunnel data. Configurations with vertical axis, positive right wing down, deg both fin sets deflectable (tandem-control) are analyzed to investigate the effectiveness of canard-only, tail-only,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Fluent is used throughout the aerospace industry as a research and design tool. Although it is semiempirical, it has been shown by a number of authors to compare favourably with experimental research (9)(10)(11)(12) . The use of computational fluid dynamics has been validated against MISL3 (6) and wind tunnel tests (7,8) .…”
Section: Methodsmentioning
confidence: 99%
“…Fluent is used throughout the aerospace industry as a research and design tool. Although it is semiempirical, it has been shown by a number of authors to compare favourably with experimental research (9)(10)(11)(12) . The use of computational fluid dynamics has been validated against MISL3 (6) and wind tunnel tests (7,8) .…”
Section: Methodsmentioning
confidence: 99%
“…1,8 The test objective was to provide an aerodynamic database to study and evaluate tandem control effectiveness. The model consists of a 3-caliber ogive nose followed by a 12-caliber cylinder with cruciform inline canards and aft tail fins.…”
Section: Tandem Control Missile Modelmentioning
confidence: 99%
“…Previous research has shown that the VFI effects are critical to the performance of the munition because the downwash of the canard vortices can reduce the effectiveness of the tail fins with potentially detrimental effects [2,[9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The interactions depend strongly on how the canards are deflected (i.e., for roll, pitch, or yaw control) and the angles of attack under consideration.…”
mentioning
confidence: 99%
“…Much of this research on the VFI has been conducted on the NASA Blair missile configuration at supersonic speeds [9,10] for a slender body (large length-to-diameter ratio) with canards and tail fins aligned in roll orientation. The results of the Blair wind-tunnel studies have been used to improve engineering-level and intermediate-level aerodynamic prediction codes [15][16][17], which use panel methods, vortex-cloud methods, or other semi-empirical methods to account for the vortices shed from the canards and body. The aerodynamic prediction codes give reasonable results over the parameters for which they have been validated and can model the flow interaction effects for a supersonic missile.…”
mentioning
confidence: 99%